(untitled) (PerCursos, 2022)
This article about the urbanization of Luanda, capital of Angola, is an essay that aimed to analyze and produce a reading on the main metamorphoses that occurred in the metropolitan region as a whole and its specificities. For its materialization, the theory of the two circuits of the urban economy of underdeveloped countries proposed by Milton Santos in 1979 in his work “O Espaço Dividido” was used as a theoretical-methodological support. It was noticed with the study that Angolan society is marked by deep socio-spatial inequalities, especially in urban spaces. The city of Luanda is the personification of these inequalities that translate into the existence, on the one hand, of a reduced central space “the formal city”, constituted by the “modernized” old urban nucleus (in the downtown) with the centralization of the offer of goods and services and with a predominance of activities from the upper circuit of the urban economy and, on the other hand, there is the extensive periphery (the informal city dominated by musseques), with a reduced supply of goods and services and where the lower circuit activities of the urban economy. Despite the existence of a national strategy to promote housing (which resulted in the emergence of new urbanizations, centralities and social housing), aimed at discouraging the practices of illegal occupation of land and favoring orderly urban growth, the fact is that the continuous expansion of the urban sprawl fueled by informality.